1982
DOI: 10.1037/0096-3445.111.2.176
|View full text |Cite
|
Sign up to set email alerts
|

Skilled performance: Effects of adult age and experience on elementary processes.

Abstract: SUMMARYDespite a general neglect in contemporary research of the role of practice on the performance of simple components of skill, considerable evidence indicates that experience leads to substantial improvement in detection, discrimination, ani speeded classification. One goal of the present research was to identify the mechanisms responsible for practice-related improvement in such elementary tasks. A second goal was to determine whether there are adult age differences in the magnitude of practicerelated im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
136
1
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(166 citation statements)
references
References 98 publications
28
136
1
1
Order By: Relevance
“…Consistent with many other cognitive aging studies (e.g., Cerella, 1985;Salthouse & Somberg, 1982), the young adults showed an advantage relative to the elderly adults in the rate of information processing. However, contrary to generalized slowing models of age-related changes in rate of information processing (Cerella, 1990;Myerson et al, 1990), the componential analysis of the retrieval trial Rig suggested that the group difference in speed of processing might not have been uniform across basic processes.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Consistent with many other cognitive aging studies (e.g., Cerella, 1985;Salthouse & Somberg, 1982), the young adults showed an advantage relative to the elderly adults in the rate of information processing. However, contrary to generalized slowing models of age-related changes in rate of information processing (Cerella, 1990;Myerson et al, 1990), the componential analysis of the retrieval trial Rig suggested that the group difference in speed of processing might not have been uniform across basic processes.…”
Section: Discussionsupporting
confidence: 76%
“…In fact, the elderly were more likely to use the less time-consuming retrieval strategy than were the younger adults. The Nebes (1978) and Salthouse and Somberg (1982) findings of no age difference in verbal production RTs suggests that the intercept difference might not be related to age differences in the rate of verbally producing an addition answer, although Charness (1987) found that young adults showed about a 28-ms advantage over elderly adults on a similar verbal production task. Thus, it is possible that a portion of the intercept difference is related to age differences in rate of verbally producing an answer, although the 28-ms estimate (Charness, 1987) would not explain the entire intercept difference.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…When adapting behavioral procedures to elderly clients, special recognition must be made of the fundamental physiological changes in the elderly (Salthouse & Somberg, 1982) and the frequent decline in the health of these clients. Attempts to adapt the Foxx and Azrin (1973) toilet training procedure for use with the elderly provide an excellent lesson.…”
Section: Behavioral Gerontology In Institutional Settingsmentioning
confidence: 99%